Discurso midiático da ideologia de gênero e sua ressonância nos planos estadual e municipais de educação do Tocantins - Maia, Marcos Felipe Gonçalves (Universidade Federal do Tocantins, 2017)
This dissertation approaches to the theme of the gender ideology and its reverberation in the regional media of Tocantins after the approval of the State and Municipal Education Plans (2015-2025). It aims to understand the meanings of the expression "gender ideology" from the discourses, motives and / or justifications that have been expressed in Tocantins online regional newspapers for the suppression of sexuality and gender issues of the municipal and state education plans of this Federative state. It uses the qualitative approach and the method of ethnomethodology and critical etnopesquisa, etnopesquisa formation in a multirreferencial way. It brings a bibliographical research to explore the concepts of identity, diversity, difference, gender, sexuality, ideology, gender ideology and educational plan. The documentary research was carried out with three regional newspapers online: Jornal do Tocantins, T1 Notícias and JM Notícia. Thirty-three ethnotexts were collected in all: nine of Jornal do Tocantins, five of T1 News and nineteen of JM News. All these ethnotexts were read from Discourse Analysis. As a result, it is possible to highlight the grouping of ten subsuming notions to understand the expression "gender ideology": 1) "Gender ideology" as being contrary to the natural and "biological" conception of male and female gender; 2) "Gender ideology" as a gay practice, or the gay movement; 3) "Gender ideology" as a possibility of destruction of the [traditional] family; 4) "Gender ideology" as a promoter of precocious sexuality; 5) "Gender ideology" as a misunderstanding of the concept of gender; 6) "Gender ideology" as a usurper of family moral education; 7) "Gender ideology" as non-scientific knowledge; 8) "Gender ideology" as an authoritarian theory; 9) "Gender ideology" as a producer of inconveniences; 10) "Gender ideology" as contrary to a society where the Bible, together with the Federal Constitution and the Civil Code, are pillars of society. We conclude that the use of the word ideology in the expression "gender ideology" is based on a pejorative valuation according to the critical slope of ideology; Its use has been made with the intention of creating a Theocratic State in Brazil in particular by the taking of Education as a field of dispute and of formation of this society; as well as the "Gender Ideology" has also been used to disqualify other forms of scientific knowledge and knowledge that tries to show and denounce the different ways of being male and female in the societies.